Snobbery : - Epstein, Joseph (Houghton Mifflin, 2002)
Noted essayist and former American Scholar editor Epstein, having enlightened us on ambition (Ambition: The Secret Passion), now turns to its companion, snobbery. The topic is ripe with promise, but Epstein's observations are less revelatory than entertaining. Underneath their pretentious exteriors, he writes, snobs are insecure people who have latched onto arbitrary measures of status to prove they're worthier than those around them. It's natural fallout, he says, in a world where complete fairness is nonexistent. The best antidote to snobbery, Epstein suggests, is to treat people the same, regardless of their circumstances, and to value things for their intrinsic worth rather than their cachet. Epstein shares his own snobbish tendencies and biases at the outset. From childhood, he writes, his snob radar was fully operational, and by his senior year in high school he was already "an impressively cunning statustician." Epstein goes on to deal with a range of past and present pretensions relating to class, work, democracy, possessions, parenting, college, clubs and intellectualism. In one delicious instance, he describes an American reaction to visiting royalty. "Princess Diana, not long before she died, visited Northwestern University, where I teach," he writes. "The spectacle of the university president, a smallish man in glasses, following the Princess about the campus, yapping away, reminded one of nothing so much as that of a Chihuahua attempting to mount an Afghan hound." The chapter on name-dropping is particularly sharp, citing a variety of ways people exploit connections to well-known individuals for social profit. Epstein has a wickedly wonderful sense of humor and keen observational skills, both on display in the firsthand anecdotes scattered throughout this essayistic assemblage